2005
DOI: 10.1007/s10653-004-5671-7
|View full text |Cite
|
Sign up to set email alerts
|

Elemental composition of Jamaican foods 1: A survey of five food crop categories

Abstract: The concentrations of 27 elements in Jamaican food categories consisting of fruit, legumes, leafy and root vegetables and other root crops are reported. The main analytical techniques used were neutron activation analysis and flame and graphite furnace atomic absorption spectrophotometry. The results are compared, where possible, with values from Denmark, the United Kingdom, the United States and Nigeria, and with some regulatory limits. Over 75% of the results for antimony, arsenic, barium, cerium, thorium an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 12 publications
0
62
1
Order By: Relevance
“…Analysis: Cadmium concentrations were determined by graphite furnace atomic absorption spectrophotometry (GF-AAS) using a PerkinElmer 5100 PC Spectrophotometer (10). A standard reference material, NIST 1570a (Trace Elements in Spinach Leaves), was also included with every 10 samples as a check on the accuracy of the determination of the total cadmium content.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis: Cadmium concentrations were determined by graphite furnace atomic absorption spectrophotometry (GF-AAS) using a PerkinElmer 5100 PC Spectrophotometer (10). A standard reference material, NIST 1570a (Trace Elements in Spinach Leaves), was also included with every 10 samples as a check on the accuracy of the determination of the total cadmium content.…”
Section: Methodsmentioning
confidence: 99%
“…But despite warnings to the public and the availability of modern medicines (7), bush teas remain quite widely used and some teas may be introduced as early as in the first six months of life (8). The early work did not address trace elements which have become of interest because of naturally elevated levels of heavy metals in some Jamaican soils (9) and foods (10).…”
Section: Introductionmentioning
confidence: 99%
“…The lowest sodium level was found be in green peppers at 4 mg/kg. Mineral concentrations in a range of vegetables have been reported by (Howe et al 2005). Calcium, copper, chromium, iron, magnesium, manganese, potassium, sodium and zinc values will be given for some vegetables for the highest observed values expressed on a fresh weight basis.…”
Section: Vegetablementioning
confidence: 96%
“…Levels of calcium and potassium were very much greater than the concentrations of the other elements: potassium being slightly higher than calcium, irrespective of the work up procedure: ultrasonic extraction or wet or dry ashing methods (Alvarez et al 2003). A thorough analyses of a wide range of metals in Jamaican foods has been reported to (Howe et al 2005) for legumes, leafy and root vegetables, fruit and other root crops. Only some metals levels will be mentioned here for the first three products listed above.…”
Section: Vegetablementioning
confidence: 99%
“…In a similar study, Ismail et al (2011) using Atomic Absorption Spectrometry (AAS) reported higher concentrations of Ca in okra (210 mg/kg), tomato (335 mg/kg), chilli pepper (305 mg/kg), onion (265 mg/kg), cucumber (180 mg/kg) and carrot (220 mg/kg). Howe et al (2005) working in Ethiopia and using Neutron Activation Analysis (NAA) as well as Flame and Graphite Furnace Atomic Absorption Spectrophotometry (FGFAAS) in a study of elemental composition of five categories of Jamaican foods reported 360 mg/kg Ca as against 139 mg/kg; 133 mg/kg; 135 mg/kg and 7.65 mg/kg Ca recorded for same foods in Denmark, UK, USA and Nigeria, respectively. Accessions with significant concentration of this element could be developed for use in supplementation of other sources of Ca to meet the recommended dietary intake.…”
Section: Concentrations Of Ten Essential Elements In 22 Accessions Ofmentioning
confidence: 99%